Advances in ecopolitics. Vol. 2 - Barry, John, 1966- (Bingley, U.K. : Emerald, 2008)
Since the 17th century people have sought out utopias, establishing communities towards this aim. In the UK and US, educational institutions and planned communes were developed. Many were seeking to establish green alternative lifestyles or agrarian co operatives. Others reclaimed land or settled in areas once populated and then abandoned, providing a new lease of life for rural areas. Ireland has witnessed these patterns of utopian resettlement from the establishment of gaeltachts in the 1920s through to the influx of environmentally minded idealists from the UK or Germany to the west during the 1970s and 1980s. More recently, communities have emerged around protest sites in Rossport, the Glen of the Downs, Carrickmines and Tara and an Ecovillage in Tipperary has been established.
Ecofeminism and a politics of performative affinity : direct action, subaltern voices, and the green public sphere / Chaone Mallory -- Transition towns :'survival','resilience' and sustainable communities : outline of a research agenda / Stephen Quilley -- Environmental exploitation : an analysis and taxonomy / Gerald Nagtzaam -- Return to the villages / Mark Somma -- Green Ireland? : waste in its social context / Michael Murray -- The dilemma of justice : foreign oil multinationals and human rights violation in the Niger Delta of Nigeria / Victor Ojakorotu -- Commentary : the Irish Green Party and the referendum for the EU reform treaty of Lisbon / Liam Leonard -- Commentary :'A letter from Bali', J. Timmons Roberts, College of William and Mary US / Peter Doran.
Keywords: Environmental policy; Political ecology